2014
DOI: 10.1111/jnc.12838
|View full text |Cite
|
Sign up to set email alerts
|

Sialyltransferase ST3Gal IV deletion protects against temporal lobe epilepsy

Abstract: Temporal lobe epilepsy (TLE) often becomes refractory, and patients with TLE show a high incidence of psychiatric symptoms, including anxiety and depression. Therefore, it is necessary to identify molecules that were previously unknown to contribute to epilepsy and its associated disorders. We previously found that the sialyltransferase ST3Gal IV is upregulated within the neural circuits through which amygdalakindling stimulation propagates epileptic seizures. In contrast, this study demonstrated that kindling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 66 publications
(79 reference statements)
4
10
0
Order By: Relevance
“…In contrast, St3gal4-knockout (KO) mice exhibit no epileptic seizures [5]. Furthermore, emotional behavioral tests, including open-field tests, forced swim tests, and fear conditioning tests, showed depression-and anxiety-like symptoms in these mice [5]. We found that kindling stimulation increased growth hormone (GH) levels in neuronal cells and upregulated St3gal4 [14].…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In contrast, St3gal4-knockout (KO) mice exhibit no epileptic seizures [5]. Furthermore, emotional behavioral tests, including open-field tests, forced swim tests, and fear conditioning tests, showed depression-and anxiety-like symptoms in these mice [5]. We found that kindling stimulation increased growth hormone (GH) levels in neuronal cells and upregulated St3gal4 [14].…”
Section: Introductionmentioning
confidence: 91%
“…We found that kindling stimulation increased growth hormone (GH) levels in neuronal cells and upregulated St3gal4 [14]. In contrast, St3gal4-KO mice showed downregulation of GH and insulin-like growth factor 1 (Igf1) mRNA in the cerebral cortex [5]. Because GH and IGF1 are the main hormones involved in lipid metabolism, we investigated the relationships between St3gal4 and lipid metabolism using different types of oils to determine the effects of oils on the emotional behaviors of KO mice [15].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations